Lab-scale pop-rice equipment is upscaled and simplified for dissemination in West Africa. - CGIAR Research Program on Rice (2021)
Pilot-scale pop-rice equipment was designed and prepared at AfricaRice, however actual usage of the equipment was keeping as postponed due to travel ban by COVID-19. Since we have lab-scale equipment at JIRCAS, we had obtained optimum conditions for pop-rice production, using NERICA 1 and 3 from JIRCAS experimental field.